Enhancing Fourth-Grade Students' Learning Outcomes in Integrated Science and Social Studies Through Problem-Based Learning - Meinar R Age; Nashrullah Nashrullah; Muchdar Muchdar; Abdul Rahman; Sukri Sukri (Papanda Publisher, 2026)
The integration of Science and Social Studies (IPAS) in Indonesia's Merdeka Curriculum requires pedagogical approaches that foster critical thinking and problem-solving skills. However, fourth-grade students at SD Inpres 1 Tondo demonstrated low critical thinking abilities and passive learning behaviors, with only 37.04% achieving mastery in IPAS. This study examined the effectiveness of Problem-Based Learning (PBL) in improving student learning outcomes in IPAS subjects. A classroom action research design following the Kurt Lewin model was employed over two cycles with 27 fourth-grade students. Data collection utilized observation sheets, achievement tests, interviews, and documentation. Quantitative data were analyzed using percentage formulas for individual and classical mastery, while qualitative data underwent thematic analysis. The implementation of PBL produced substantial improvements across all measured dimensions. Classical mastery increased dramatically from 37.04% (pre-action) to 44.44% (Cycle I) and 92.59% (Cycle II), exceeding the 80% success criterion. Teacher performance improved from 77.41% to 94.35%, while student engagement increased from 72.32% to 88.39% across cycles. Classical absorption rate rose from 53.52% to 78.70%. Problem-Based Learning effectively enhances both learning processes and outcomes in IPAS for elementary students. The iterative refinement through action research cycles proved essential for maximizing PBL's effectiveness in integrated curriculum contexts.